Um olhar sobre (nos)otros: o documentário brasileiro na representação das identidades culturais em territórios fronteiriços - Gallina, Justina Franchi (2018)
This thesis is the result of an investigation of how short and medium-length Brazilian documentary filmmaking represents cultural identities in Brazilian continental border areas and how these representations evoke knowledge about alterities and differences in frontier territories. In order to do so, seven documentaries produced between 2000 and 2015, directed by Brazilian filmmakers from the border states with the countries of Uruguay, Argentina, Peru and Bolivia, were analyzed: A Gente Luta mas Come Fruta (AC, 2006), A Linha Imaginária (RS, 2014), Causos e Cuentos de Fronteira (RS, 2009), Continente dos Viajantes (RS, 2004), Doble Chapa (RS, 2014), Manoel Chiquitano Brasileiro (MT, 2013) e Quilombagem (RO, 2007). The methods used in the interpretative exercise were the filmic analysis, added by documentary and bibliographical research. From the decoupage, the documentaries were agglutinated in two axes of analysis that translate different ways of representing the border: the "Border as a place of permanence", in which the set of films represents social dynamics that propitiate the territorial fixation of the subjects and social groups by the recognition or appropriation of the non-dominant cultures; and the "Frontier as a space of resistance", in which the documentaries assembled portray social dynamics hostile to territorial fixation by the negation and discrimination of non-dominant cultures, provoking displacements and struggle for survival in the symbolic, physical and material sense. The analysis of the documentaries pointed to the predominance of integrative identity senses in the films that represent the frontier zones of the south of Brazil and of identity meanings based on the difference in documentaries that represent the frontier zones of the Amazon region. In general, most films analyzed used a limited repertoire of technical resources with a tendency to operate from the classical narrative structure, whereby space-time linearity and the coherence of the senses tell a story in a logical way. The prevailing mode of expository representation in the organization of narratives, with the use of statements, explanatory lettering and assembling of evidence, preponderated the interactive / reflective ethics in the form of relationship between the directors and the characters. The different viewpoints of representation adopted by the directors have made it possible to identify representations that go beyond the idealization or simplification of cultural identities in frontier territories, because while some films have reiterated certain stereotypes, other documentaries have highlighted the perspective of social groups that are far from having their images and voices expressed in the productions of the reference media, since they were - and continue to be - kept on the sidelines.